Letter (copy) : Ray Cox Memorial - Citrine, Walter, 1887-1983
042-0085-001 WMC/WJB/MS/187 International. 16th December, 1937. Mr. W. Schevenels, International Federation of Trade Unions, 9, avenue d'Orsay, Paris. VIIe. Dear Mr. Schevenels, RAY COX MEMORIAL. We have again received from the Southampton Trades Council a reminder that we have not yet sent them the promised photograph of the Ray Cox Memorial. Would you be good enough to communicate again with the Spanish comrades urging them to obtain it? The Council referred to is one of our most generous and active supporters, and we are placed in a somewhat embarrassing position by constantly having nothing definite to send to them. With the compliments of the Season. Yours faithfully, General Secretary. 292/946/42/85